AKR1B10 and digestive tumors development: a review - Shen, Yao; Qiu, Ailin; Huang, Xin; Wen, Xiaosha; Shehzadi, Sundar; He, Yan; Hu, Qian; Zhang, Jian; Luo, Dixian; Yang, Shenghui (Frontiers in Immunology, 2024)
Aldo-keto reductase family 1 member B10 (AKR1B10) is a member of the AKR1B subfamily. It is mainly found in cytoplasm, and it is typically expressed in the stomach and intestines. Given that its expression is low or absent in other tissues, AKR1B10 is a potential diagnostic and therapeutic biomarker for various digestive system diseases. Here, we review recent research progress on AKR1B10 in digestive system tumors such as hepatocellular carcinoma, gastric carcinoma, colorectal carcinoma, pancreatic carcinoma, oral squamous cell carcinoma, laryngeal squamous cell carcinoma, cholangiocarcinoma, and nasopharyngeal carcinoma, over the last 5 years. We also discuss the current trends and future research directions for AKR1B10 in both oncological and non-oncological diseases to provide a scientific reference for further exploration of this gene.